2014
DOI: 10.1016/j.worlddev.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Historicizing Sustainable Livelihoods: A Pathways Approach to Lead Mining in Rural Central China

Abstract: This article adopts a "pathways to sustainability" approach to study lead mining in rural China. Through an in-depth case study, it reveals how shifting mining practices are tied to institutional and political economic contexts, cost-benefit distribution, and changes in livelihood resources and strategies. It weaves together an analysis of livelihood practices with a study of attitudes to livelihood and environment, which are usually researched separately. In turn, it demonstrates that a longitudinal analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…These findings mirror research on small‐scale mining within China – for instance Lu and Lora‐Wainwright's () study in Hunan Province – which found that livelihood benefits are highly differentiated, with wealthier investors who began mining earlier profiting at a much higher rate than more marginalized individuals entering at later times. Future research could focus on the cleavages and power differentials that exist within and across groups of Chinese miners, and examine the differentiated impact that the Ghanaian gold rush has had on their livelihoods and the welfare of their households back in China.…”
Section: Resultssupporting
confidence: 79%
“…These findings mirror research on small‐scale mining within China – for instance Lu and Lora‐Wainwright's () study in Hunan Province – which found that livelihood benefits are highly differentiated, with wealthier investors who began mining earlier profiting at a much higher rate than more marginalized individuals entering at later times. Future research could focus on the cleavages and power differentials that exist within and across groups of Chinese miners, and examine the differentiated impact that the Ghanaian gold rush has had on their livelihoods and the welfare of their households back in China.…”
Section: Resultssupporting
confidence: 79%
“…Chinese mines are mostly still relatively small, which makes regulating them efficiently a challenge (Lu and Lora-Wainwright, 2014;Shen et al, 2009). Artisanal and small-scale mining is a vital source of work in areas with few other options, employing millions of people and accounting for over half of China's mineral production (Shen et al, 2009).…”
Section: Other Potential Threatsmentioning
confidence: 99%
“…China's demand for mineral raw materials has grown by an average of 10% per year over the past 3 decades and has contributed to the recent global mining boom (Hilpert & Mildner 2013). Chinese mines are mostly still relatively small, which makes regulating them efficiently a challenge (Shen et al 2009;Lu & Lora-Wainwright 2014). Artisanal and small-scale mining is a vital source of work in areas with few other options, employing millions of people and accounting for over half of China's mineral production (Shen et al 2009).…”
Section: Other Potential Threatsmentioning
confidence: 99%
“…This points to the likelihood that the individual Chinese miners in Ghana have benefited in significantly different ways-with some potentially even being exploited. After all, research on smallscale mining within China has shown that the contribution to the livelihoods of miners is highly differentiated, with wealthier investors profiting at a much higher rate than more marginalised individuals (Lu and Lora-Wainwright 2014). Research has also documented the ways in which poor Chinese migrant workers are often exploited through the withholding (and sometimes nonpayment) of wages by 'labour subcontractors' (baogongtou) operating in townships and villages (Pun and Xu 2011).…”
Section: 000mentioning
confidence: 99%